Parâmetros produtivos e morfogênicos de pastagens de milheto ou capim sudão em pastejo de vacas de descarte - Pacheco, Rangel Fernandes (2013)
The objective of this study was to evaluate the productive and morphogenesis in pastures sudan grass or millet, on the behavioral aspects and performance of cull cows. Were used 22 cull cows from the cross between Charolais and Nellore, age and average initial live weight of 8 years and 448 kg, kept under continuous grazing pearl millet (Pennisetum americanum (L.) Leeke) or sudan grass (Sorghum bicolor cv. sudanense). The experimental period was 63 days, divided into 3 periods (21 days each). The experimental design was completely randomized with two treatments and five repetitions (area) for the variables related to the productive pastures; ten replicates (animals) to behavioral parameters, and three replications (area) for the morphogenesis of grasses. There were no differences (P<0.05) for the productive and behavioral function in animal treatments. Pastures millet showed higher (P<0.10) canopy height (32.69cm vs 20.29 cm), number of leaves per tiller (4.74 vs 3.06), number of green leaves (4.26 vs 2.55), number of adult leaves (2.34 vs 1.08), number of young leaves (1.92 vs 1.47) and leaf appearance rate (0.147 vs 0.080), compared to pastures sudan grass. The rates of dry matter, crude protein and supply of leaf blade, were higher in the first 21 days of use of pastures (130.77 kg/ha of dry matter (DM), 170.4 g / kg DM and 3.63%; respectively). The stocking was similar in the first two periods (2329.2 and 1843.5 kg / ha PV), and over the last experimental period (1261.5 kg / ha of PV). Average daily gain and gain body condition score were similar across periods (mean of 1.00 kg/day and 0.23 points, respectively). The time devoted to grazing (613 minutes), number of steps per minute (8.8) and number of feeding stations per minute (10.9) were higher in the first experimental period, while the rate of bites per minute (47.41) was higher in the third trial. Sudan grass pastures are similar regarding the parameters of productive grazing millet with similar reflections on the performance and behavior of animals. However, the present potential of millet pastures above the vegetative sudan grass. With the advance of the growing season pastures for significant changes in the structures of pastures, which reflect the performance and behavior of animals.